Qualidade acústica em salas de aula: contribuições à gestão da manutenção - Souza, Robert Silva de (2021)
As an introduction, it is registered that the environments in which the human being develops his activities can affect both his physical and his emotional state. Lighting, noise, temperature, ventilation, odors, among other factors, need attention when preparing building projects. However, it was only in the 1970s that the first technical documents were elaborated dealing with performance criteria for small buildings, and it was only in 1984 that the need to consider acoustic comfort, included in the ISO 6241/1984 standard, became explicit. In Brazil, the Brazilian Association of Technical Standards (ABNT) published NBR 15,575 in 2008, which was later revised and published in 2013, aiming at better quality of constructions through the adoption of new concepts such as acoustic performance. However, there are still buildings that were built before that period, when the parameters were different. This means that it is not uncommon to find workplaces with low-quality in acoustic comfort, as in universities. Thus, it was suspected that a building at the Federal University of Espírito Santo was outside the norms in this regard and, after a preliminary survey, it was verified the existence of several complaints related to areas of a specific environment, thus constituting the problem of research. Therefore, the objective of this work was to map these areas in order to identify which ones would present acoustic factors that contribute to discomfort. The adopted methodology consisted of the survey of areas with acoustic deficiency through the application of questionnaires and interviews with teachers, the survey of reference measures and acoustic factors, based on bibliographic research and, also, on-the-spot measurements. After being treated, the data were compared with the normative reference parameters. In theoretical terms, the field found support in the ABNT norms, in particular the NBR10,151 / 2019 and the NBR 10,152 / 2017, in the interference and importance of acoustics in work environments and in theories that deal with noise and its impacts on human beings and your job performance. As a result, it was obtained the mapping of the rooms that presented acoustic problems, which can interfere in the performance of teachers and students. The technical / technological product resulting from the dissertation consists of a mapping containing the places where the acoustic deficiency was found and suggestions for improvements, entitled 'Acoustic diagnosis of classrooms in the Multimedia Building of the Ufes Arts Center and suggestions for corrective projects'.